Features of the surname of Kazakh repatriates and its social-documentary consequences (Journal of history, 2024)
The article discusses the ways of forming the surname of Kazakhs from far abroad and its impact on documentary naturalization and social integration. The purpose of the study is to consider some of the problems arising from the peculiarities of the surnames of Kazakh repatriates from different points of view (linguistic, legal) and discuss this using specific examples. To achieve this goal, such tasks as identifying the concept of "surname" in the Kazakh worldview, its alternatives, the role of patronymic surnames and studying the factors that influenced the formation of the surname of Kazakh repatriates were put forward. The results of the study showed that the surnames of Kazakhs in most cases are astronomical names. In some countries, Kazakhs used surnames such as patronymic surnames (China, Mongolia), eponyms (Iran), the title of birthplace, names associated with the Kazakh culture (Turkey). But the way to register their full name and documents was developed on the basis of various state laws and official languages. Usually, their full names in the identity documents consist of two components (surname, first name). The fact that such documents create obstacles to their social life after returning to Kazakhstan is revealed on the basis of interviews with Kazakh repatriates. The society, accustomed to a documentary structure consisting of three components (surname, first name, patronymic), sometimes gets confused from the names of Kazakh repatriates, cannot distinguish where the surname is and where the name is. Summing up these causes and consequences, it was concluded that during the transformation of the various documents of the Kandases did not provide for a unified state standard, as a result of which the documents were not properly structured.Keywords. Kazakhs, repatriate, surname, anthroponymy, patronymic, eponym, passport, citizenship.